Nanoparticulate polyelectrolyte complexes of thermally sensitive poly(l-lysine)-based copolymers and DNA. (May 2018) - Veleva-Kostadinova, Emilia; Dimitrov, Ivaylo; Toncheva-Moncheva, Natalia; Novakov, Christo; Momekova, Denitsa; Rangelov, Stanislav
Graphical abstract: Highlights: Hybrid copolymers of the type (PNIPAm)77 -g-(PEG)9 -b-poly(l -lysine)z were synthesized. Micelle-like nanosized particles were obtained by abrupt heating of their dilute aqueous solutions. The micelle-like structures exhibited strong ability to condense DNA. Well-defined, colloidally stable, and non-toxic polyplex particles were formed. The hybrid copolymers are promising gene-delivery vector materials. Abstract: The present contribution describes the synthesis and feasibility of using a series of hybrid copolymers, designed and evaluated as stimuli-sensitive, polypeptide-based gene-delivery vectors. The copolymers of the type (PNIPAm)77 -g-(PEG)9 -b-(PLL)z were prepared by a combination of free radical copolymerization and ring-opening polymerization of N-carboxyanhydride of protected l -lysine with successive protective groups cleavage. They comprised fixed composition of thermally responsive poly(N-isopropylacrylamide) (PNIPAm) to which hydrophilic, non-ionic (poly(ethylene glycol), PEG) chains were grafted and a polycationic (poly(l -lysine), PLL) block with increasing from 10 to 65 degrees of polymerization. The abrupt heating of dilute aqueous solutions above the transition temperature resulted in formation of nanosized particles, which exhibited strong ability to condense DNA into well-defined polyplex particles. The latter displayed exceptional colloidal stability at room temperature. Preliminary in vitro studies showed that both polyplexes and the pure copolymers of the lowest degree of polymerization of the polypeptide block were devoid of intrinsic cytotoxicity. The findings indicate that the (PNIPAm-g-PEG)-b-PLL copolymers can be considered prospective as gene-delivery platforms.